Political unrest, the Arab Spring, and FDI flows: A quantitative investigation - Nayef Al-Shammari; John Willoughby; Mariam S. Behbehani (Cogent Economics & Finance, 2023)
The Middle East region is recognized by observers as one of the most politically unstable areas worldwide. Due to the significant growth of foreign direct investment in the MENA region during the period before the recent political turmoil, this study empirically tests the impact of these political disturbances on foreign direct investment over time across Arab Spring countries. The study uses panel techniques to estimate the regression models by applying pooled OLS, fixed effect, and random effect. In addition, the Hausman test is used in order to choose the appropriate estimated model between fixed effects and random effects. The sample covers five countries in the MENA region that experienced the Arab Spring uprising during the period (2011-2014). The whole yearly data set ranges from 1980 to 2014. The data describes the periods before and during the Arab Spring turmoil (2011-2014). According to the appropriate fixed effect approach, results show that the economic, social, and political factors are all crucial contributors to FDI movements and volumes in Arab Spring countries. Interestingly, the Arab Spring era plays a very important role in the deterioration of FDI in these countries. The movement of FDI in the Arab Spring region is related to episodes of political instability. This political unrest has created an adverse impact on foreign investment, and this indicates a lack of trust of potential international investors. This study also confirms that other economic and social factors are significant contributors to FDI in the MENA region.
Keywords: E22; O11; O16; O38; P16; 330; Arab Spring; foreign direct investment; MENA; political instability